Children's understanding of demonstratives: an experimental study with German-speaking children between 5 and 7 years of age - Glauer, Ramiro David; Sixtus, Elena; Kachel, Gregor; Lonnemann, Jan; Hildebrandt, Frauke (Frontiers in Psychology, 2024)
Demonstratives ("This"/"that") express a speaker-relative distance contrast and need to be substituted for each other systematically: depending on their relative position, what one speaker refers to by saying "this" another speaker has to refer to by saying "that". This substitution aspect of demonstratives poses additional difficulties for learning demonstratives because it requires recognizing that two speakers have to refer to the same thing with different words, and this might be one reason for the reportedly protracted acquisition of demonstratives. In an online study conducted in German, it was investigated whether children in the estimated upper age range of demonstrative acquisition (5 to 7 years) understand demonstratives' substitution aspect with familiar ("dies"/"das") and novel ("schmi"/"schmu") demonstratives, and whether they understand novel words ("schmi"/"schmu") when used non-demonstratively as labels (N = 73; between-subject). Children's accuracy was compared with adult performance (N = 74). The study shows that children between 5 and 7 years of age perform less accurately than adults in all conditions. While adults' performance was highly accurate in all conditions (between 75% and 92% correct), children performed below chance in both demonstrative conditions and above chance in the labelling condition. This suggests that children do not understand demonstratives in the presented setup. More detailed analyses of children's response patterns indicate that they instead treat words as mutually exclusive labels in any condition.